2,2’-Diphenyl-1-picrylhydrazyl and 2,2′-azinobis-(3-ethyl-benzothiazoline-6-sulfonic acid) scavenging assay of Extract and Fractions of Rambutan (Nephelium Lappaceum L.) Seed - Budikafa, MJ; Rumiyati, -; Riyanto, S; Rohman, A (Dhaka University Journal of Pharmaceutical Sciences, 2019)
This research was intended to evaluate the antiradical activity of extracts and fractions of rambutan seed using 2,2’- diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+). The powder of rambutan seed was subjected to maceration with methanol. The methanolic extract obtained was then fractionated using petroleum ether (PE), dichloromethane (DCM) and ethyl acetate (EA) to obtain PE, DCM and EA fractions, respectively. The methanol extract and fractions were then assayed for antiradical activities and phenolics and flavonoid contents.The results showed that EA fraction has lowest IC50 values among extract and fractions evaluated, i.e. 244.6 ± 2.1 μg/ml using DPPH radical. Using ABTS radical, EA fraction (0.1%) also revealed the highest antiradical activity of 643.4 ± 34.9 μM trolox equivalent. However, these antiradical activities were lower than those in positive controls used (vitamin C and vitamin E). The antiradical activities of extract and fractions correlated with total phenolics and flavonoid contents. The seed of rambutan fruit could be exploited as natural antioxidants to be used in food supplements. Dhaka Univ. J. Pharm. Sci. 18(2): 145-152, 2019 (December)